Rapid detection of FAdV-4 by one-tube RPA-CRISPR/Cas12a assay - Ma, Lei; Wang, Xueping; Zhang, Mingliang; Zhu, Mengjie (Frontiers in Microbiology, 2025)
IntroductionFowl adenovirus serotype 4 (FAdV-4) is a highly contagious viral pathogen of global significance that affects various avian species. It primarily infects poultry and wild birds, leading to avian inclusion body hepatitis (IBH) and hepatitis-hydropericardium syndrome (HHS). The development of rapid diagnostic tools for detecting FAdV-4 is crucial for effective disease control and eradication efforts.MethodsIn this study, we developed a recombinase polymerase amplification (RPA) combined with CRISPR/Cas12a assay, specifically targeting the FAdV-4 Hexon gene. RPA and CRISPR/Cas12a reagents were added to the bottom and lid of the test tube at once, allowing the detection process to occur within a single reaction tube. This approach reduced contamination.ResultsThe RPA-CRISPR/Cas12a detection method can identify as few as 10 copies of the genome per reaction, demonstrating 100% sensitivity comparable to that of fluorescence PCR (qPCR). This approach exhibits high specificity for FAdV-4, with no cross-reactivity observed with other FAdV serotypes or common avian pathogens. Additionally, the agreement rate between the results of RPA-CRISPR/Cas12a and qPCR for detecting clinical samples is as high as 97.5%.DiscussionTherefore, the RPA-CRISPR/Cas12a assay presents a promising alternative for the simple, sensitive, and specific identification of FAdV-4.